Locally Advanced Breast Cancer Patient's Recurrence Rates Comparison Received Steroidal and Nonsteroidal Aromatase Inhibitor Based on Luminal - Desak Gede Agung Suprabawati; Bernadeta Hernik Setiyandari; Dwi Hari Susilo; Bara Kharisma; Rizki Amalia (Wolters Kluwer - Medknow Publications, 2024)
Introduction: Aromatase inhibitors are hormonal therapies used in menopausal breast cancer with positive progesterone receptors and/or estrogen receptors. A third-generation aromatase inhibitor is divided into two categories: reversible nonsteroids and irreversible steroids. According to the previous studies, there are no consistent research findings on the recurrence after aromatase inhibitor therapy in luminal-type locally advanced breast cancer (LABC). Methods: This study is an analytical observational study with a retrospective cohort design. The data taken are secondary data from medical records on patient visits with luminal-type LABC in the oncology clinic in 2018-2021. The statistical test was the Chi-square test to determine the relationship between age, luminal subtype, radiotherapy, steroid and nonsteroid aromatase inhibitors, and the recurrence rate. Results: It was found that 30% of luminal B patients who received steroidal aromatase inhibitor and 68.43% who received nonsteroidal aromatase inhibitor experienced recurrence, with an odds ratio (OR) of 5.056 (1.560-16.384; P = 0.012). Meanwhile, in luminal A patients, 17.2% of patients who received steroidal aromatase inhibitor and 68.2% who received nonsteroidal aromatase inhibitor experienced recurrence, with an OR of 10.286 (2.757-38.370; P = 0.000). Based on multivariate analysis, the luminal type had no significant impact on the increased risk of recurrence (P = 0.141), but the administration of aromatase inhibitor had a significant impact (P = 0.000). Conclusion: Luminal A LABC patients who received nonsteroidal aromatase inhibitors had a 10.286-fold higher risk of recurrence compared to those who received steroidal aromatase inhibitors.